MENINGKATKAN AKTIVITAS SISWA KELAS XI MA AL-KHAIRAAT GORONTALO MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE BERKIRIM SALAM DAN SOAL PADA MATERI LARUTAN PENYANGGA DAN HIDROLISIS GARAM (Suatu Penelitian di Kelas XI IPA MA Al-Khairaat Gorontalo TP 2008/2009) - Sari, Eka Puspita; Bialangi, Nurhayati; Ischak, Netty (Jurnal Entropi, 2009)
The purpose of class action research is to increase the students activity on buffer and salt hydrolysis by using cooperative learning type sending greeting and question. The students of class XI IPA MA Al-Khairaat Gorontalo city as the subject of the research fourteen (14) people, consist five for boys and nine for girls. T6he successful qualification of this research are : (1) minimum 75 % from all the teacher activity and students that observed achieve the target, (2) minimum 80% of students thet gooten action get mark 6,5 upper with the understanding of material average 65%. Students activity in learning process is influenced by the result of students learning. Presentate average of students activity in cycle I : 27,88% get excellent, 51,07% get good, 17,86% get intermediate, 3,57% get bed. The result of students learning 71,43% with the understanding of material 64,8%. Cycle II : presentate average of students activity 68,57% get excellent, 27,14% get good, 4.,29% get intermediate, the result of students learning 85,72% and the understanding of material 80,25% Base on the data of research result, then the hypotesis of action tested the truth, namely :by using cooperative learning model type sending greeting and question in buffer and salt hydrolysis, then the students learning activity increase